Thermal conductivities of hydrogen encapsulated boron nitride and hybrid boron nitride – carbon nanotubes using molecular dynamics simulations. (August 2022) - Dethan, Jacob F.N.; Yeo, Jingjie; Rhamdhani, M. Akbar; Swamy, Varghese
Abstract: In this work, we investigated the thermal conductivities of boron nitride nanotubes (BNNTs) and carbon nanotubes (CNTs) as potential hydrogen storage materials using atomistic nonequilibrium molecular dynamics (NEMD) simulations. Pristine and defective (containing B/N/C single atom vacancy or B-N double atom vacancies) capped armchair BNNTs and BN-C heteronanotubes have been studied. Furthermore, thermal conduction in BNNT, CNT, and BN(50%)-C(50%) heteronanotubes with varying amounts of encapsulated H2 molecules has been evaluated. We compare the performance of the reactive forcefield ReaxFF with non-reactive Tersoff-adaptive intermolecular reactive empirical bond order (AIREBO)-Lennard-Jones (TALJ) potentials combination. The ReaxFF potential yielded consistently lower thermal conductivity ( k ) for all the nanotubes. However, it provides a better qualitative prediction of thermal transport in the nanotubes (in terms of k reduction due to defects and entrapped H2, and sensitivity to composition as reflected in the phonon density of states) whereas Tersoff/TALJ potentials provide a better quantitative prediction of k while failing to account for acoustic phonon details. Near-linear mixing rule for k across the CNT-BNNT composition suggested by both potentials indicates smooth interfacial heat transport at the heterojunctions. Graphical Abstract: ga1